Sab and the abominable black condition - Baker, Gabriell (2023)
Since the settlement of the colonies in America, the black condition has been rejected and turned into something unsightly. This negative connotation has affected the way black people perceive themselves. This can be seen in the novel Sab (1841) by Gertrudis Gómez de Avellaneda, where the protagonist was influenced by this system and saw himself as a slave. This paper reflects on this self-perception.